Activated carbon as back contact for HTM-free mixed cation perovskite solar cell - Singh, Rahul; Jun, H.K.; Arof, Abdul Kariem (Taylor & Francis, 2018)
Carbon materials have potential applications in perovskite solar cell because of their excellent electronic properties and low cost. In this paper, we report, for the first time, activated carbon as a back contact for hole transport layer-free mixed halide perovskite solar cells. The ability of activated carbon to form conducting chain-like structure when dispersed in a polymeric solution makes it a possible candidate for back contact. A composite of activated carbon and PEMA was optimized with varying concentration. Mixed cation was used as a perovskite absorber and was analysed for its structural and optical properties. The fabricated devices were studied for their electrical performance. They were also subjected to stability study and showed promising results.